Auditee and Auditor Factors Affecting Audit Delay with Audit Firm Reputation as Moderating Variable: Supporting SDG 16 in Tourism Firms - Dedy Christiyanto; Rahmawati Rahmawati; Evi Gantyowati; Taufiq Arifin (Journal of Current Studies in SDGs, 2027)
Objective: To examine the effects of auditee and auditor factors on audit delay and evaluates whether audit firm reputation moderates these relationships. The analysis focuses on tourism, restaurant, and hotel companies listed on the Indonesia Stock Exchange, while linking timely audited reporting to the transparency and accountability principles of Sustainable Development Goal 16. Method: The study employed a quantitative explanatory design using secondary data from audited annual reports for 2017–2021. Purposive sampling yielded 22 companies and 110 firm-year observations. Liquidity, firm size, financial distress, and audit opinion were tested as explanatory variables, while audit firm reputation was examined through moderated regression analysis. Results: Liquidity had no significant effect on audit delay. Firm size and financial distress significantly increased audit delay, whereas an unqualified audit opinion reduced the reporting lag. Audit firm reputation did not moderate the liquidity–audit delay relationship but significantly moderated the effects of firm size, financial distress, and audit opinion. Novelty: The study integrates auditee financial characteristics and auditor-related attributes within a single moderation model in a sector observed across pre-pandemic and pandemic periods. It extends audit-delay research by demonstrating that reputable audit firms do not uniformly accelerate reporting; their moderating role depends on the underlying company characteristic. The findings offer sector-specific evidence relevant to stronger corporate reporting discipline and the accountability orientation of SDG 16.